Dynamic spectrum allocation based on one-band multi-winner auction - Wen-zhu ZHANG; Ling-yun WANG (Tongxin xuebao)
In order to improve the effectiveness of traditional auction in DSA (dynamic spectrum allocation) issue in cognitive radio networks,a new dynamic spectrum allocation algorithm based on one-band multi-winner auction was proposed.Compared with the original greedy algorithm,the new algorithm can achieve better spectrum allocation solutions with lower computational complexity by introducing the multiple greedy strategy.It increases the seller's revenue by improving the VCG (vickery-clarke-groves) mechanism,while retaining the dominant strategy incentive compatible property.In addition,it suppresses the occurrence of collusion effectively.Simulation results show that the algorithm proposed can get spectrum allocation efficiency close to the optimal solution and increase the auction revenue significantly.